If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6x = 12 + 3x Solving 3 + -6x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + -6x + -3x = 12 + 3x + -3x Combine like terms: -6x + -3x = -9x 3 + -9x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -9x = 12 + 0 3 + -9x = 12 Add '-3' to each side of the equation. 3 + -3 + -9x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + -9x = 12 + -3 -9x = 12 + -3 Combine like terms: 12 + -3 = 9 -9x = 9 Divide each side by '-9'. x = -1 Simplifying x = -1
| 8m+6(m-8)=50 | | 5=4.9-(-x) | | -33=3-4(k+1) | | 4+7x+1=10 | | 0.5x+3=0.3x-5 | | x^4+-9x^2+2=0 | | 0.4x^2+5.4x+14.8=0 | | (2r+6)(2r-6)= | | (2r+6)(2r-6)= | | (2r+6)(2r-6)= | | -9=3(4b+8)-b | | 5=49-(-x) | | 25-8s=5-3s | | .5x-7=11 | | 7g-12=3+2.33g | | (4v-4)(5v-6)= | | 35=-.875x | | 3x^2-60x+108=0 | | .75x=.6 | | 7n^2=27n+4 | | 5n+3+4n= | | 5x-6=6x-1 | | 3x+-7=8x+23 | | 4x=16x+1 | | 4(x+3)=(4x+12) | | 2+11z+12=10z+12 | | y=-4(2)+2 | | 46=7-3x | | 5(90-7x)x=-126 | | y=-4(1)+2 | | y=-4(0)+2 | | 45r-22x=182 |